Emotional Intelligence and Resilience of High School Teachers in Diocesan Schools in Antique - Florence C. Sencio, MSLT; Celo I. Magallanes (Philippine Social Science Journal, 2020)
In our globalized society, understanding emotions and developing resilience can help us move adeptly through the current challenges and future ones.  Emotional intelligence is the capacity of individuals to understand their emotions and those of other people.  It is an ability to label and adjust emotions appropriately, use and manage behavior and relationships, and help them adapt to environments. On the other hand, resilience refers to an individual's capacity to maintain and renew themselves, particularly in the presence of stressors; that is, they can withstand stressors without manifesting psychological dysfunction. Teaching is regarded as among the most stressful jobs today.  Knowing how to cope despite setbacks or barriers, or limited resources is a must for teachers; otherwise, they will easily quit or give up. Hence, the paper describes the level of emotional intelligence and resilience of high school teachers of a Diocesan Catholic School in Antique during the School Year 2019-2020. Additionally, it measures the differences in the level of emotional intelligence and resilience when grouped according to demographic variables. The study also explores the relationship between emotional intelligence and resilience of teachers.